2019
DOI: 10.1101/581678
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gene regulatory network reconstruction using single-cell RNA sequencing of barcoded genotypes in diverse environments

Abstract: Understanding how gene expression programs are controlled requires identifying regulatory relationships between transcription factors and target genes. Gene regulatory networks are typically constructed from gene expression data acquired following genetic perturbation or environmental stimulus. Single-cell RNA sequencing (scRNAseq) captures the gene expression state of thousands of individual cells in a single experiment, offering advantages in combinatorial experimental design, large numbers of independent me… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 95 publications
0
51
0
Order By: Relevance
“…Breakthroughs at a few levels might soon yield the technology necessary to read bioinformatic regulatory signals in these yeast at a much greater level of precision. A screen of pathway perturbations linked to high throughput gene expression readout, such as single cell or single colony RNA-seq (Jackson et al, 2019;Liu et al, 2019), combined with machine learning approaches would make great strides towards identifying such a bioinformatic regulatory signal for the PKA pathway. This would be strengthened by a tighter link between pathway mutants and transcription factor binding via traditional assays such as ChIP-seq and complementary methods such as the calling card method (Mayhew and Mitra, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Breakthroughs at a few levels might soon yield the technology necessary to read bioinformatic regulatory signals in these yeast at a much greater level of precision. A screen of pathway perturbations linked to high throughput gene expression readout, such as single cell or single colony RNA-seq (Jackson et al, 2019;Liu et al, 2019), combined with machine learning approaches would make great strides towards identifying such a bioinformatic regulatory signal for the PKA pathway. This would be strengthened by a tighter link between pathway mutants and transcription factor binding via traditional assays such as ChIP-seq and complementary methods such as the calling card method (Mayhew and Mitra, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Yeast ( S. cerevisiae ) has previously been examined by single cell sequencing using the Fluidigm C1 system but this handles less than 100 cells 41 . Jackson et al 42 sequenced~40K S. cerevisiae cells with the commercial Chromium (10X Inc.) system. We opted to build a fungal DROP-seq modified from the original approach presented in Macosko et al 43,44 , to address issues of cost and flexibility in comparison with commercial alternatives.…”
Section: Nanolitre Droplet-based Single Cell Rna-sequencing (Drop-seqmentioning
confidence: 99%
“…Whereas Macosko et al recommends a ratio of 100K cells to 120K beads for DROP-seq, we found that a ratio of 1M cells for 120K beads generated a sufficient yield of cDNA as per the Agilent Tapestation. Jackson et al 42 used 5M cells as input to the Chromium (10X Inc.) system. Furthermore, whereas Macosko et al use 1ml of lysis buffer, we used 1.2 ml, and instead of 13 PCR cycles, we used 17 ( Jackson et al used 10 cycles).…”
Section: Fungal Drop-seq Protocolmentioning
confidence: 99%
“…Defining a functional map of the cell that connects regulators with their targets is essential for understanding, and engineering, cellular behavior (Chasman et al , ). The budding yeast Saccharomyces cerevisiae is an ideal organism for defining and studying gene regulatory networks (Hughes & de Boer, ) using global methods from DNA microarrays (Hughes et al , ) to single‐cell RNA sequencing (Jackson et al , ).…”
Section: Experimental Design For Network Inferencementioning
confidence: 99%